Mass culture as a factor weakening the social and humanitarian potential of the family - Фабрика, А. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article deals with the negative impact of mass culture on important functional manifestations of the family and various aspects of its life. The study has found the mass culture as a factor that leads to the weakening of the family social and humanitarian potential.